EFEKTIVITAS METODE PEMBELAJARAN READING GUIDE DALAM PENINGKATAN DAYA INGAT ANAK SLOW LEARNER - Mohammad Bagas Nur Cahyo; Isroul Zamzami Fauziyah; Aisyah Salwa Dinda Aulia; Mintowati (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2025)
This study aims to determine the effectiveness of the Reading Guide method in improving the memory of slow learners who have difficulty reading. The scope of the study includes the characteristics of slow learners, the learning process, and the supporting and inhibiting factors of this method. The study used a qualitative descriptive approach with secondary data from the YouTube Channel video